The International Right to Health: What Does It Mean in Legal Practice and How Can It Affect Priority Setting for Universal Health Coverage?. Issue 1 (2nd January 2016) - Dittrich, Rebecca; Cubillos, Leonardo; Gostin, Lawrence; Chalkidou, Kalipso; Li, Ryan
Abstract: Abstract —The international right to health is enshrined in national and international law. In a growing number of cases, individuals denied access to high-cost medicines and technologies under universal coverage systems have turned to the courts to challenge the denial of access as against their right to health. In some instances, patients seek access to medicines, services, or technologies that they would have access to under universal coverage if not for government, health system, or service delivery shortfalls. In others, patients seek access to medicines, services, or technologies that have not been included or that have been explicitly denied for coverage due to prioritization. In the former, judicialization of the right to health is critical to ensure patients access to the technologies or services to which they are entitled. In the latter, courts may grant patients access to medicines not covered as a result of explicit priority setting to allocate finite resources. By doing so, courts may give priority to those with the means and incentive to turn to the courts, at the expense of the maximization of equity- and population-based health. Evidence-based, informed decision-making processes could ensure that the most clinically and cost-effective products aligning with social value judgments are prioritized. Governments should be equipped to engage in and defend rational priority setting, and the priority setting process and institutions involved should be held accountable through an opportunity for appeal and judicial review. As a result, the courts could place greater reliance on the government's coverage choices, and the population's health could be most equitably distributed.